Intracardiac and Cerebral Thrombosis Complicated With Mycoplasma Pneumonia - Huang, Weisheng; Hao, Jingxia; Zhang, Yingqian (Curēus (Palo Alto, CA), 2024)
A seven-year-old girl developed multiposition thrombosis after fever and respiratory symptoms. Chest computed tomography (CT) scan demonstrated bilateral infiltrates, consolidation of the right lower lobe, and pleural effusion in the right lung field. Brain magnetic resonance imaging (MRI) showed multiple abnormal signals in the brain with limited diffusion, and cerebral infarction could not be excluded. Echocardiography revealed hypoechoic mitral valve tips, which are likely to be suspected as vegetation. infection was clarified by a four-fold increase in IgG antibodies to sera. D-dimer levels were elevated increasingly. We found and reported this rare pediatric case of an -induced severe pneumonia complicated with intracardiac and cerebral thrombosis. We investigate the clinical characteristics, diagnosis, and treatment of refractory mycoplasma pneumonia complicated with intracardiac and cerebral thrombosis in children.